Research of environmentally hazardous geological processes using electroprospecting methods - Sapuzhak, O.Ya.; Syroiezhko, O.V.; Deshchytsya, S.A.; Pidvirnyi, O.I.; Kolyadenko, V.V.; Maryash, I.M.; Klymkovych, B.Ya. (Geofizicheskiy Zhurnal, 2025)
Electroprospecting methods are successfully used to solve problems related to environmentally hazardous geological processes. The study was carried out using the time domain electromagnetic method at various objects of local and regional importance. We detected anomalies of apparent resistivity are connected with the zones of development of hazardous geological processes: filtration-suffusion and subsidence on the territory of the Ivano-Frankivsk National Technical University of Oil and Gas, sulfate karst on the territory of a school in the Bartativ, Lviv oblast, on a construction site in Lviv and along the railway track in Chernivtsi oblast; salt karst on the territories of the Stebnyk and Kalush-Holyn potash deposits. The results confirmed the effectiveness of solving geoecological problems using the time domain electromagnetic method.